2019
DOI: 10.1071/an17895
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the simulated physiological oocyte maturation (SPOM) system on F1 Gyr × Holstein oocytes and embryos

Abstract: The present study aimed to evaluate the effect of the simulated physiological oocyte maturation (SPOM) system on F1 Gyr × Holstein oocytes and embryos by evaluating the meiotic arrest, embryo production rates, total number of cells and lipid score. Three experiments were conducted and the following three experimental groups were formed according to in vitro maturation (IVM) treatments: CONTROL 1 (TCM 199 medium without FBS), CONTROL 2 (commercial medium) and SPOM (TCM 199 medium with forskolin and 3-isobutyl-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In equine, the addition of both forskolin (50 μM) and IBMX (100 μM) in the pre‐maturation medium tended to improve the maturation rate of equine oocyte (37% vs. 25%), however without significant effect (Metcalf et al., 2020). Furthermore, it has been reported that forskolin supplemented to the pre‐maturation medium in bovine and pigs can increase oocyte cAMP levels (Park, Lee, et al., 2016), decrease intra‐oocyte H 2 O 2 and increase intra‐oocyte glutathione and maintain meiotic arrest (Leal et al., 2019). A high level of forskolin in the culture medium produced a superior apoptosis rate, leading to lower quality of oocytes (Wu et al., 2020).…”
Section: Impacts Of Forskolin On In Vitro Oocyte Maturationmentioning
confidence: 99%
“…In equine, the addition of both forskolin (50 μM) and IBMX (100 μM) in the pre‐maturation medium tended to improve the maturation rate of equine oocyte (37% vs. 25%), however without significant effect (Metcalf et al., 2020). Furthermore, it has been reported that forskolin supplemented to the pre‐maturation medium in bovine and pigs can increase oocyte cAMP levels (Park, Lee, et al., 2016), decrease intra‐oocyte H 2 O 2 and increase intra‐oocyte glutathione and maintain meiotic arrest (Leal et al., 2019). A high level of forskolin in the culture medium produced a superior apoptosis rate, leading to lower quality of oocytes (Wu et al., 2020).…”
Section: Impacts Of Forskolin On In Vitro Oocyte Maturationmentioning
confidence: 99%
“…Forskolin is an AC activator that stimulates the production of cAMP (Thomas, Thompson, Armstrong, & Gilchrist, 2004). Forskolin can increase oocyte cAMP concentrations (Park et al, 2016), maintain meiotic arrest (Albuz et al, 2010; Leal et al, 2019), improve embryonic development (Albuz et al, 2010; Park et al, 2016), increase intra‐oocyte glutathione and decrease intra‐oocyte H 2 O 2 (Li et al, 2016). The dibutyryl cAMP (dbcAMP) molecule is a membrane‐permeable analog of cAMP that mimics the function of endogenous cAMP.…”
Section: Introductionmentioning
confidence: 99%